The Implementation of Senior High School Biology Practicum in Batang Regency - Ilma, Nailul; Marianti, Aditya; Ngabekti, Sri (Universitas Negeri Semarang)
The application of Curriculum 2013 emphasizes more on the scientific approach. Scientific approach can be realized by implementing practicum aimed at developing various domains of learning objectives, such as attitude, skill, and knowledge. This study aims at analyzing the relationship between human resource readiness factors, infrastructure, curriculum, and practicum implementation with the enforcement of senior high school biology practicum in Batang regency. This study employs quantitative approach particularly survey method. The sample are taken by using nonprobability sampling technique, namely purposive sampling, sample of 6 public and private classes of senior high schools. In the process of analysis, the researcher analyzed the data about factors obtained by using path analysis and correlation analysis. Based on the path analysis, it can be concluded that there is a correlational relationship between the factors that influence the implementation of high school biology practicum in Batang Regency.